Crocin ameliorated skin tissue inflammation in atopic dermatitis in mice - Alyoussef, Abdullah (International Journal of Research in Dermatology, 2020)
Background: Atopic dermatitis (AD) is considered a chronic recurrent inflammatory skin disease. In addition, crocin is the major carotenoid compound found in Gardenia jasminoides. It is previously proved to produce anti-inflammatory actions. Therefore, we conducted this research to investigate the therapeutic effects of crocin on a mice model of AD. Methods: Mice were investigated for the number of scratches and dermatitis score. Skin was isolated and used for measurements of gene and protein expression of β-catenin, NFκB, TNF-α and IL-1β. Results: Authors found that crocin significantly reduced the number of scratches, ear thickness and dermatitis score. In addition, crocin ameliorated AD-induced elevation in the expression of β-catenin, NFκB, TNF-α and IL-1β. Conclusions: Crocin ameliorated DNCB-induced AD in mice via blockage of β-catenin with subsequent reduction in inflammatory pathway.